Innovating sustainable agriculture: Perspectives from economy and biology professionals - Albert Gamot Malau; April Gunawan Malau; Marudut Bernadtua Simanjuntak (University of Muhammadiyah Malang, 2024)
In the realm of agricultural development, the pursuit of sustainability stands as a paramount objective, necessitating an integration of multifaceted expertise from diverse disciplines. Amidst this pursuit, understanding the perspectives of professionals in both the realms of economy and biology becomes imperative, serving as a cornerstone for innovative strategies. This study examines the viewpoints of economy and biology professionals on multidisciplinary innovations for sustainable agricultural development. Through qualitative analysis of interviews and focus groups, the research identifies key themes and challenges. Participants recognise the need for integrating diverse disciplines to address agricultural sustainability, emphasising the importance of economic viability and technological innovation. However, barriers such as high costs and limited access to resources hinder widespread adoption. Policy recommendations include incentivising sustainable practices and fostering collaboration between stakeholders. The results underscore the significance of multidisciplinary approaches in advancing sustainable agriculture, with implications for policy and practice.